The insulin-like growth factor system in chronic kidney disease: Pathophysiology and therapeutic opportunities - Youngman Oh (The Korean Society of Nephrology, 2012)
The growth hormone-insulin-like growth factor-insulin-like growth factor binding protein (GH-IGF-IGFBP) axis plays a critical role in the maintenance of normal renal function and the pathogenesis and progression of chronic kidney disease (CKD). Serum IGF-I and IGFBPs are altered with different stages of CKD, the speed of onset, the amount of proteinuria, and the potential of remission. Recent studies demonstrate that growth failure in children with CKD is due to a relative GH insensitivity and functional IGF deficiency. The functional IGF deficiency in CKD results from either IGF resistance due to increased circulating levels of IGFBPs or IGF deficiency due to increased urinary excretion of serum IGF-IGFBP complexes. In addition, not only GH and IGFs in circulation, but locally produced IGFs, the high-affinity IGFBPs, and low-affinity insulin-like growth factor binding protein-related proteins (IGFBP-rPs) may also affect the kidney. With respect to diabetic kidney disease, there is growing evidence suggesting that GH, IGF-I, and IGFBPs are involved in the pathogenesis of diabetic nephropathy (DN). Thus, prevention of GH action by blockade either at the receptor level or along its signal transduction pathway offers the potential for effective therapeutic opportunities. Similarly, interrupting IGF-I and IGFBP actions also may offer a way to inhibit the development or progression of DN. Furthermore, it is well accepted that the systemic inflammatory response is a key player for progression of CKD, and how to prevent and treat this response is currently of great interest. Recent studies demonstrate existence of IGF-independent actions of high-affinity and low-affinity-IGFBPs, in particular, antiinflammatory action of IGFBP-3 and profibrotic action of IGFBP-rP2/CTGF. These findings reinforce the concept in support of the clinical significance of the IGF-independent action of IGFBPs in the assessment of pathophysiology of kidney disease and its therapeutic potential for CKD. Further understanding of GH-IGF-IGFBP etiopathophysiology in CKD may lead to the development of therapeutic strategies for this devastating disease. It would hold promise to use of GH, somatostatin analogs, IGFs, IGF agonists, GHR and insulin-like growth factor-I receptor (IGF-IR) antagonists, IGFBP displacer, and IGFBP antagonists as well as a combination treatment as therapeutic agents for CKD.